A Structural Model for the Ligand Binding of Pneumococcal Serotype 3 Capsular Polysaccharide-Specific Protective Antibodies - Ahmet Ozdilek (American Society for Microbiology, 2021)
Infectious diseases caused by pathogenic bacteria are a major threat to human health. Capsular polysaccharides (CPSs) of many pathogenic bacteria have been used as the main components of glycoconjugate vaccines against bacterial diseases in clinical practice worldwide, with various degrees of success.